PS / PE alloy composite material as well as preparation method and application thereof
By adding copolymerized PP and homopolymerized PP to the PS/PE alloy composite material, and using maleic anhydride graft and PS-g-PP as compatibility agents, the problem of poor chemical resistance of the material is solved and higher chemical resistance and strength are achieved.
Patent Information
- Application Number
- CN202411965376.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-29
AI Technical Summary
The chemical resistance of existing PS/PE alloy composites is poor, resulting in bulging and pit defects easily occur during foaming.
The modulus and corrosion resistance of the material are improved by adding copolymerized PP and homopolymerized PP to the PS/PE alloy composite material and using maleic anhydride graft and PS-g-PP as compatibilizers.
The chemical resistance and strength of PS/PE alloy composites are significantly improved, and the occurrence of defects during foaming is reduced.
Smart Images

Figure BDA0005218216930000011 
Figure BDA0005218216930000021 
Figure BDA0005218216930000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of general plastics, and in particular relates to a PE / PS alloy composite material and a preparation method and application thereof. Background Art
[0002] The blending of polystyrene resin and polyethylene resin can produce a cheap plastic alloy on the one hand, and can also achieve complementary performance on the other hand. Polyethylene resin can improve the impact strength of polystyrene resin, especially low-temperature impact performance and chemical resistance.
[0003] However, since polystyrene is a non-crystalline resin and polyethylene is a crystalline resin, the compatibility between the two is not good, and the comprehensive performance of the polystyrene-polyethylene alloy material obtained without a compatibilizer is poor. After using a common compatibilizer for volume expansion, the blend morphology is still a phase separation structure, and it is difficult to ensure that the dispersed phase is fully refined, resulting in poor comprehensive performance of the PS / PE alloy composite material, especially chemical corrosion resistance. At the same time, due to the low modulus of the polyethylene resin, the obtained PS / PE alloy composite material is relatively soft, which is prone to bulging and pit defects during the foaming process. Summary of the invention
[0004] The purpose of the present invention is to provide a PS / PE alloy composite material to overcome the defects or shortcomings of the prior art PS / PE alloy composite material, which has poor chemical resistance and easily leads to bulges and pits during the foaming process.
[0005] Another object of the present invention is to provide a method for preparing the PS / PE alloy composite material.
[0006] Another object of the present invention is to provide an application of the PS / PE alloy composite material.
[0007] To achieve the above object, the present invention is implemented by the following technical solutions:
[0008] A PS / PE alloy composite material comprises the following components calculated in parts by weight:
[0009]
[0010] The PP resin is a copolymer PP and a homopolymer PP in a mass ratio of 1:(1-3); and the compatibilizer is a mixture of maleic anhydride grafted product and PS-g-PP.
[0011] The invention provides a PS / PE alloy composite material. PS resin and PE resin are used as matrix resins, copolymerized PP and homopolymerized PP are added thereto, and the homopolymerized PP is dispersed on a phase interface under the action of a compatibilizer PS-g-PP, so that the modulus of the alloy composite material can be effectively improved, and corrosion resistance can be provided to the alloy composite material; the copolymerized PP is dispersed between the PE resin and the homopolymerized PP, plays a compatibility and barrier role, and greatly enhances the strength and chemical resistance of the system; at the same time, the reinforcing filler is also dispersed at the phase interface of the PS phase and the PE phase under the action of a maleic anhydride graft to form a reinforcing skeleton, so that the strength of the system is further improved, and the risk of PS / PE alloy being deflated and having pit defects in the preparation of refrigerator liner materials is greatly improved.
[0012] It should be noted that the PP resin described in the present invention is a copolymer PP and a homopolymer PP in a mass ratio of 1:(1-3). The specific mass ratio can be 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2, 1:2.2, 1:2.5, 1:2.8 or 1:3, etc., all of which can realize the present invention.
[0013] It should be noted that, in the PS / PE alloy composite material of the present invention, the PS resin content is preferably not less than 20 wt %.
[0014] Furthermore, the PS / PE alloy composite material comprises the following components calculated in parts by weight:
[0015]
[0016] Furthermore, the mass ratio of the maleic anhydride graft to PS-g-PP is 1:(5-2), specifically 1:5, 1:4.5, 1:4, 1:3.5, 1:3, 1:2.5 or 1:2, etc., all of which can realize the present invention.
[0017] Furthermore, the maleic anhydride grafted product is one or more of PS-g-MAH, PE-g-MAH or PP-g-MAH.
[0018] Furthermore, the maleic anhydride content in the maleic anhydride grafted product is 0.2-30 wt %.
[0019] Specifically, the test method for the maleic anhydride grafting rate is an acid-base titration method.
[0020] Furthermore, the grafting rate of PP in the PS-g-PP is 10 to 40 wt%.
[0021] Specifically, the grafting rate is determined by infrared calibration method at 972 cm -1 The absorption peak is the internal standard peak of PP, 698cm -1The absorption peak at is taken as the internal standard peak of PS, and the grafting content of PP can be determined by the ratio of the peak areas.
[0022] It should be noted that the PS-g-PP used in the present invention can be commercially available or homemade.
[0023] In some specific embodiments, the PS-g-PP can be prepared by the following preparation method:
[0024] The PP is melted, styrene monomer is added under initiator conditions, melt blended, and extruded into granules.
[0025] Specifically, the initiator may be dicumyl peroxide and / or tert-butyl perbenzoate.
[0026] Specifically, the added amount of the initiator is 0.1-0.3 wt % of PP.
[0027] The grafting rate can be controlled by adjusting the raw material addition ratio.
[0028] Specifically, the mass ratio of PP to styrene monomer is (10:90) to (40:60).
[0029] The extrusion temperature is 190° C. to 220° C., and the screw speed is 400 to 700 rpm.
[0030] The melt flow rate of the homopolymer PP is not particularly limited in the present invention. Further, the melt flow rate of the homopolymer PP is 0.2 to 25 g / 10 min at 230° C. and 2.16 kg load as tested in accordance with ISO1133-1-2011 standard.
[0031] The present invention does not specifically limit the melt flow rate of homopolymer PP. Further, the melt flow rate of the copolymer PP is 0.4-20 g / 10 min at 230° C. and 2.16 kg load as tested in accordance with ISO1133-1-2011 standard.
[0032] Furthermore, the PS resin has a melt flow rate of ≤8 g / 10 min at 200° C. and 5 kg load when tested according to ISO 1133-1-2011 standard.
[0033] Furthermore, the PS resin is HIPS.
[0034] Furthermore, the PE resin is low-density polyethylene and / or linear low-density polyethylene.
[0035] The present invention does not specifically limit the melt flow rate of homopolymer PP. Further, the melt flow rate of the PE resin is 0.5-3.0 g / 10 min at 190° C. and 2.16 kg load according to ISO1133-1-2011 standard.
[0036] Furthermore, the toughening agent includes styrene-butadiene block copolymer (SBS) and / or hydrogenated styrene-butadiene block copolymer (SEBS).
[0037] Furthermore, the filler includes one or more of barium sulfate, talc or calcium carbonate.
[0038] Specifically, the average particle size of the filler is 1 to 8 μm.
[0039] Furthermore, the nucleating agent includes one or more of an amide nucleating agent, a phosphate nucleating agent or a hydrazide nucleating agent.
[0040] Specifically, the amide nucleating agent is one or more of polyethylenediamine oxalic acid, polydecanediamine terephthalic acid, polydecanediamine isophthalic acid, polynonanediamine terephthalic acid or polynonanediamine isophthalic acid.
[0041] The phosphate ester is one or more of sodium phenylphosphinate, sodium phenylphosphite, sodium 2,2'-methylene-bis(4,6-di-tert-butylphenyl)phosphate or bis[2,2'-methylene-bis(4,6-di-tert-butylphenyl)]aluminum phosphate.
[0042] The hydrazide nucleating agent is adipic acid diphenyl dihydrazide and / or benzenesulfonyl hydrazide.
[0043] Furthermore, the PS / PE alloy composite material also includes 0.1 to 2 parts of auxiliary agents.
[0044] Specifically, the auxiliary agent is an antioxidant and / or a lubricant.
[0045] In the present invention, commonly used antioxidants may be selected, such as but not limited to one or more of hindered phenol antioxidants, phosphite antioxidants or thioester antioxidants.
[0046] Specifically, the hindered phenol antioxidant is one or more of N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyphenylpropionamide, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate, β-(4-hydroxy-3,5-di-tert-butylphenyl)propionate n-octadecyl or spiroglycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate].
[0047] Specifically, the phosphite antioxidant is 2,4-di-tert-butylphenol and / or bis(2,6-di-tert-butyl-4-tolyl)pentaerythritol phosphite.
[0048] Specifically, the thioester antioxidant is one or more of distearyl thiodipropionate, dilauryl thiodipropionate or pentaerythritol dodecapropylthioate.
[0049] In the present invention, commonly used lubricants can be selected, for example but not limited to, stearate lubricants and / or polyethylene wax.
[0050] Specifically, the stearate lubricant may be one or more of calcium stearate, magnesium stearate or zinc stearate.
[0051] The present invention also protects a method for preparing the above PS / PE alloy composite material, comprising the following steps:
[0052] S1. The PS resin, toughening agent, compatibilizer and part of the additives are uniformly mixed and melt-extruded to obtain a premixed masterbatch;
[0053] S2. The premixed masterbatch of step S1 and other components are mixed evenly, and a PS / PE alloy composite material is obtained by melt extrusion.
[0054] Specifically, the temperature of the melt extrusion in step S1 is 180-230°C.
[0055] The temperature of the melt extrusion in step S2 is 200 to 240°C.
[0056] The present invention also protects the use of the PS / PE alloy composite material in the preparation of household appliances and / or automobile accessories, such as refrigerator liner, automobile door panel or automobile instrument panel material.
[0057] Compared with the prior art, the present invention has the following beneficial effects:
[0058] The invention provides a PS / PE alloy composite material, which adopts PS resin and PE resin as matrix resins, adds copolymerized PP and homopolymerized PP in appropriate proportions, and adopts maleic anhydride grafted product and PS-g-PP as compatibilizers, and can effectively improve the defects of the alloy composite material such as poor corrosion performance in a foaming agent such as cyclopentane, and bulges and pits that are easily caused during the foaming process. DETAILED DESCRIPTION
[0059] The present invention is further described in detail below in conjunction with specific examples, which are only used to explain the present invention and are not used to limit the scope of the present invention. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0060] 1. Raw materials used in each embodiment and comparative example:
[0061] PS resin:
[0062] PS resin 1: HIPS 8265, with a melt flow rate of 3.5 g / 10 min at 200 °C and 5 kg load, purchased from INEOS Styrolution Polymer Materials Co., Ltd.
[0063] PS resin 2: HIPS 825 (HW) with a melt flow rate of 6.5 g / 10 min at 200 °C and 5 kg load, purchased from Qingdao Haiwan Chemical Co., Ltd.;
[0064] PS resin 3: HIPS1175, with a melt flow rate of 2.8 g / 10 min at 200 °C and 5 kg load, purchased from Shengxi'ao Company;
[0065] PE resin: low-density polyethylene, LDPE 2426H, with a melt flow rate of 2.2 g / 10 min at 190 °C and a load of 2.16 kg as tested in accordance with ISO 1133-1-2011, purchased from PetroChina Co., Ltd.
[0066] PP resin:
[0067] Copolymer PP1: PPB-M09-G (K8009), with a melt flow rate of 9.68 g / 10 min at 230 °C and 2.16 kg load according to ISO 1133-1-2011 standard, purchased from Sinopec;
[0068] Copolymer PP2: PP K9017, with a melt flow rate of 19 g / 10 min at 230 °C and a load of 2.16 kg as tested in accordance with ISO 1133-1-2011, purchased from Taiwan Chemical Fiber Co., Ltd.
[0069] Homopolymer PP1: PP B1101, with a melt flow rate of 0.7 g / 10 min at 230 °C and 2.16 kg load according to ISO 1133-1-2011 standard, purchased from Sinopec Corporation;
[0070] Homopolymer PP2: PP HP500N, with a melt flow rate of 12 g / 10 min at 230 °C and a load of 2.16 kg as tested in accordance with ISO 1133-1-2011, purchased from CNOOC Shell Co., Ltd.
[0071] Toughening agent: SBS YH-792E, purchased from China National Petroleum Corporation;
[0072] Compatibilizer:
[0073] PS-g-MAH: SMA-700, maleic anhydride grafting rate of 18 wt%, purchased from Jiaxing Huawen Chemical Co., Ltd.;
[0074] PE-g-MAH: MC226, maleic anhydride grafting rate 0.65wt%, purchased from Ningbo Nengzhiguang New Materials Technology Co., Ltd.;
[0075] PS-g-PP1: PP grafting rate 20wt%, homemade;
[0076] PS-g-PP2: PP grafting rate 10wt%, homemade;
[0077] PS-g-PP3: PP grafting rate 40wt%, homemade;
[0078] PS-g-PP4: BP-1310, PP grafting rate 30wt%, purchased from Jiayirong;
[0079] PS-g-PP1-3 were prepared by the following preparation method:
[0080] PP (PP HP500N) was added into an internal mixer, melted at 190°C, 0.2wt% of dicumyl peroxide and tert-butyl perbenzoate were added, and then styrene monomer was added for melt blending and extrusion granulation; the extrusion temperature was 205°C, the screw speed was 500rpm, and the grafting rate of PP was controlled by the feeding ratio;
[0081] filler:
[0082] Filler 1: talcum powder, TYT-777A, average particle size 5 μm, purchased from Guangzhou Tianyuan Chemical Co., Ltd.
[0083] Filler 2: barium sulfate, XM-8000, average particle size 3.3 μm, purchased from Guangdong Hengmeiyuan Nanotechnology Co., Ltd.;
[0084] Additives:
[0085] Nucleating agent: hydrazide nucleating agent; antioxidant: hindered phenol antioxidant; lubricant: stearate lubricant; the auxiliary agents are all commercially available. It should be noted that the same raw materials in the parallel experiments of the embodiments and comparative examples of the present invention have the same source.
[0086] 2. Examples 1 to 17 and Comparative Examples 1 to 5 were prepared according to the formulations in Tables 1 to 2 by the following preparation method:
[0087] S1. The PS resin, toughening agent, compatibilizer and part of the additives are uniformly mixed and melt-extruded to obtain a premixed masterbatch;
[0088] S2. The premixed masterbatch of step S1 and other components are mixed evenly, and a PS / PE alloy composite material is obtained by melt extrusion, wherein the temperature of the melt extrusion is 220°C.
[0089] Example 18 was prepared according to the formulation in Table 2 by the following preparation method:
[0090] The components were mixed uniformly and melt-extruded to obtain a PS / PE alloy composite material, wherein the melt-extrusion temperature was 220°C.
[0091] 3. Performance test:
[0092] (1) Modulus test: The PS / PE alloy composite materials prepared in each embodiment and comparative example were injection molded into mechanical splines with a size of 80 mm*10 mm*4 mm. The test was performed according to GB / T 9341-2008 at a temperature of 23° C., a bending speed of 2 mm / min, and a span of 64 mm.
[0093] (2) Cyclopentane resistance test: The PS / PE alloy composite materials prepared in each embodiment and comparative example were prepared into 150 mm*10 mm*4 mm tensile specimens according to GB / T 1040-2006 standard, and the standard tensile specimens were fixed with a fixed deformation of 5%. Cyclopentane foaming agent liquid was dripped on the surface of the specimen and the specimen was left to stand for 48 hours. The cyclopentane on the surface was wiped off and then the specimen was left to stand for 24 hours before the tensile performance test was performed. The tensile strength after treatment was recorded and calculated according to: retention rate = tensile strength after treatment / initial tensile strength * 100%.
[0094] Examples 1 to 18 and Comparative Examples 1 to 4
[0095] Table 1 Amount (unit: weight parts) and properties of each component in the PS / PE alloy composite material in Examples 1 to 11
[0096]
[0097] Table 2 Amount (unit: weight parts) and properties of each component in the PS / PE alloy composite materials in Examples 12 to 18 and Comparative Examples 1 to 5
[0098]
[0099]
[0100] It can be seen from Tables 1 and 2 that the PS / PE alloy composite materials prepared by the present invention have good mechanical properties and chemical resistance. Specifically, the flexural modulus is not less than 1600 MPa, the initial tensile strength is not less than 25 MPa, and the retention rate after corrosion by cyclopentane foaming agent is not less than 85%.
[0101] It can be seen from Examples 1 to 4 that when the mass ratio of styrene maleic anhydride copolymer or polyolefin maleic anhydride copolymer to PS-g-PP in the compatibilizer is further adjusted to 1:(5-2), the comprehensive performance of the obtained PS / PE alloy composite material is better.
[0102] It can be seen from Examples 1 and 7 to 9 that when the grafting rate of PS-g-PP is further adjusted to 20 to 30 wt %, the obtained PS / PE alloy composite material has better comprehensive performance.
[0103] It can be seen from Examples 1 and 10 to 11 that when the melt flow rate of the PS resin is adjusted to ≤8 g / 10 min at 200° C. and a load of 5 kg, preferably a melt flow rate ≤5 g / 10 min, the obtained PS / PE alloy composite material has good modulus and resistance to foaming agent corrosion.
[0104] It can be seen from Comparative Examples 1 and 2 that if the mass ratio of copolymer PP and homopolymer PP in the PP resin used is not within the scope of the present invention, the corrosion resistance of the obtained alloy composite material to the foaming agent becomes weaker, which may be due to a significant change in the phase structure of the alloy composite material.
[0105] It can be seen from Comparative Examples 3 and 4 that if a single compatibilizer is used, a rigid organic or inorganic skeleton cannot be constructed in the PS / PE alloy system, resulting in a low modulus, and the phase structure of the PS / PE alloy system will also change, resulting in poor resistance to cyclopentane foaming agents.
[0106] It can be seen from Comparative Example 5 that if too little PP resin is added, the bending modulus of the obtained alloy composite material decreases, and the corrosion resistance of the foaming agent decreases.
[0107] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A PS / PE alloy composite material, characterized in that: The composition comprises the following components calculated by weight: The PP resin is a copolymer PP and a homopolymer PP in a mass ratio of 1:(1-3); and the compatibilizer is a mixture of maleic anhydride grafted product and PS-g-PP.
2. The PS / PE alloy composite material according to claim 1, characterized in that: The mass ratio of the maleic anhydride grafted product to PS-g-PP is 1:(5-2).
3. The PS / PE alloy composite material according to claim 1, characterized in that: The maleic anhydride grafted product is one or more of PS-g-MAH, PE-g-MAH or PP-g-MAH.
4. The PS / PE alloy composite material according to claim 1, characterized in that: The grafting rate of PP in the PS-g-PP is 10 to 40 wt %.
5. The PS / PE alloy composite material according to claim 1, characterized in that: The PS resin has a melt flow rate of ≤8 g / 10 min at 200° C. and 5 kg load when tested according to ISO 1133-1-2011 standard.
6. The PS / PE alloy composite material according to claim 1, characterized in that: The PE resin includes low-density polyethylene and / or linear low-density polyethylene.
7. The PS / PE alloy composite material according to claim 1, characterized in that: The filler includes one or more of barium sulfate, talc or calcium carbonate.
8. The PS / PE alloy composite material according to claim 1, characterized in that: It also includes 0.1 to 2 parts of auxiliary agents.
9. A method for preparing the PS / PE alloy composite material according to any one of claims 1 to 8, characterized in that: The steps include: S1. The PS resin, toughening agent, compatibilizer and part of the additives are uniformly mixed and melt-extruded to obtain a premixed masterbatch; S2. The premixed masterbatch of step S1 and other components are mixed evenly, and a PS / PE alloy composite material is obtained by melt extrusion.
10. Use of the PS / PE alloy composite material according to any one of claims 1 to 8 in the preparation of household appliances and / or automobile accessories.